Experimental study of the thermal properties of a fatty acid-modified graphite composite phase change material dispersion system. (September 2022) - Fang, Guihua; Zhao, Maosen; Sun, Pengbo
Abstract: In this study, modified graphite (MEG) with a strong affinity for fatty acids was synthesized via the ultrasonic dispersion method in myristic acid ethanol solution and used as a heat conduction additive. A fatty acid composite phase change material (PCM) with excellent comprehensive thermal performance was prepared with the resultant MEG. Scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction showed that the synthesis of MEG and composite PCM was due to the physical adsorption and no chemical reaction was involved. The results of thermal conductivity and differential scanning calorimetry measurements showed that the thermal conductivity of the composite PCM increased by 139.3 % after adding 2 wt% MEG. Interestingly, the latent heat of the synthesized composite was between 182.6 and 187.1 J/g after 200 heat storage and release cycles, which is comparable to that of the pure fatty acid eutectic. Thermal cycling, thermogravimetric analysis, and the thermal conductivity changes of the upper and lower layers of the composite PCM demonstrate that the composite has good dispersion stability and thermal cycling stability. Moreover, these results may provide feasible strategies for successfully synthesizing new high-performance composite PCMs and further improving energy storage efficiency. Graphical abstract: Unlabelled Image Highlights: Modified expanded graphite with strong lipophilicity were fabricated. Modified expanded graphite has excellent dispersion stability in composite PCM. Thermal conductivity of the composite PCM increases by 139.3 % after adding 2 wt% MEG. The latent heat of composite (2 wt%) is as high as 182.6–187.1 J/g after cycling stability. The composite has outstanding dispersion stability and excellent thermal cycle stability.